A Comparison of the Standpoint on Life and Death between Chinese and Thai People - Han, Xi (Journal of Sinology (วารสารจีนวิทยา), 2008)
The standpoint on life and death includes the understanding of life-death and the consideration of the meaning of life. All people no matter their class have their own points of view on life and death. Different races also have different views on it. That is because the one race’s life-death standpoint bases on the belief system of that race. The different belief systems determine the different standpoints on life and death. So firstly, we should analyze the belief systems of Chinese and Thai people to compare the standpoints on life and death between these two races. The Thai belief system includes soul belief, Brahmanism and Buddhism. And the Chinese belief system includes Confucianism, Taoism and Buddhism. The author introduced the Thai and Chinese belief systems and the differences on ghost belief, immortality, the attitude to life and death and the life – death ceremony between these two countries in this article.